Total m6A RNA levels and VIRMA expression as potential diagnostic and prognostic markers in oral squamous cell carcinoma - Kaori Shima; Yudai Shimojukkoku; Yasunobu Oku; Kanako Higashimoto; Takahiro Tsuchiyama; Yuka Kajiya; Miyako Kurihara-Shimomura; Tomonori Sasahira (Diagnostic Pathology)
Abstract Background Oral squamous cell carcinoma (OSCC) is associated with poor prognosis due to extensive local invasiveness and lymph node metastasis, often leading to a significant decrease in aesthetics and function after surgery. Therefore, elucidation of the molecular mechanisms underlying OSCC is necessary for its early detection and treatment. N6-methyladenosine (m6A) modification of mRNA is the most common form of post-transcriptional RNA methylation and is often involved in the progression of cancer by regulating the expression of various genes. Recent studies reported the tumor-promoting effects of vir-like m6A methyltransferase associated (VIRMA, also termed KIAA1429), a novel molecule involved in m6A modification; however, its role in OSCC remains poorly understood. Methods In the present study, we determined the total m6A levels and VIRMA expression in OSCC using immunohistochemistry of tissue specimens and evaluated their association with clinicopathologic characteristics. We also performed gene expression analysis of VIRMA/KIAA1429 using public datasets. Results We found that the m6A levels were significantly higher in the OSCC specimens of patients with a more advanced clinical stage (P = 0.0063), lymph node metastasis (P = 0.0323), and venous invasion (P = 0.0380) compared to those without. The analysis of the public datasets revealed that VIRMA/KIAA1429 expression levels were higher in head and neck SCC than in normal mucosa, whereas immunohistochemistry revealed that VIRMA-expressing OSCC was associated with a significantly shorter disease-free survival (P = 0.0043) and was an independent poor prognostic factor (P = 0.0179). Conclusions These results highlight the potential utility of RNA methylation and VIRMA expression for the diagnosis and treatment of OSCC.